A PSBFEM Approach for Solving Seepage Problems Based on the Pixel Quadtree Mesh - Mingjiao Yan; Yang Yang; Zongliang Zhang; Chao Su; Tianfu Luo (Geofluids)
This paper presents a PSBFEM approach that integrates the quadtree mesh generation technique based on digital images for solving seepage problems. The quantitative representation of the distribution of geometrical information and material parameters is achieved by utilizing the color intensity of each pixel, which can then be applied to seepage analysis. The presented method addresses the issue of hanging nodes by treating them as nodes of a polygonal element. We validate the proposed technique by solving three benchmark seepage problems. Results show that the image-based domain can be automatically discretized using a quadtree decomposition of the images. Furthermore, the computational efficiency and precision of the PSBFEM surpass that of the standard FEM. Therefore, the proposed technique allows for the convenient automatic discretization of the domain using pixel meshes to solve seepage problems in engineering applications.